2022
DOI: 10.1088/2058-6272/ac61c0
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of liquid meniscus formation in the ionic liquid electrospray process

Abstract: Ionic liquid electrospray thrusters (ILETs) have advantages of high specific impulse, compact structure and low power, which are excellent candidates for the propulsion system of nanosatellites. Electrospray is the working principle of ILETs. Though tremendous efforts have been made to investigate electrospray, some aspects, such as the evolution of the menisci on the micropores of porous emitter tips and the transient response of the meniscus during the polarity alternation, need to be further understood. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Note that the present simulation only calculated the electrical parameters of the discharge process of coaxial electrospray at specific condition (Q NaCl = 1.5 nL s −1 , Q IL = 1 nL/s, V = 4.1 kV, the same as the condition in figure 7) without considering the movements of the fluids. The electric field simulation is formulated by solving the charge conservation equation, similar method has been used in previous studies [56][57][58].…”
Section: Numerical Simulation Of the Discharge Of Coaxial Electrospraymentioning
confidence: 99%
“…Note that the present simulation only calculated the electrical parameters of the discharge process of coaxial electrospray at specific condition (Q NaCl = 1.5 nL s −1 , Q IL = 1 nL/s, V = 4.1 kV, the same as the condition in figure 7) without considering the movements of the fluids. The electric field simulation is formulated by solving the charge conservation equation, similar method has been used in previous studies [56][57][58].…”
Section: Numerical Simulation Of the Discharge Of Coaxial Electrospraymentioning
confidence: 99%
“…Recently, some CFD codes have been employed to simulate the dynamic behavior of cone formation of aqueous solution or ionic liquid. Sen et al simulated the cone-jet electrospray on carbon nanofiber emitters using a CFD code (FLOW-3D) and demonstrated the feasibility of these simulations [18]. Liu et al simulated the meniscus formation of an ionic liquid in the electrospray process and found that the alternation of polarity can delay the cone growth time [19].…”
Section: Introductionmentioning
confidence: 99%
“…1009-0630/22/070101+02$33.00 liquid meniscus formation in the ionic liquid electrospray process [8], simulation of the helicon plasma source in magnetoplasma rocket engine [9], numerical study of effect of aft-loaded magnetic field on multiple ionizations in Hall thruster [10], and the characteristics of plasma in a novel laser-assisted pulsed plasma thruster [11]. These papers reflect the latest progress in electric propulsion technology in universities, research institutes and aerospace industry departments of China.…”
mentioning
confidence: 99%